A novel ANK1 frameshift mutation associated with neonatal hereditary spherocytosis: a case report - Qing, Xin; Zhu, Jimo; Zhu, Xiaoshi; Zhang, Yu; Deng, Junchao; Tang, Binzhi (Frontiers in Pediatrics, 2025)
BackgroundHereditary spherocytosis (HS) is a genetically inherited hemolytic anemia resulting from erythrocyte membrane defects, predominantly associated with genetic mutations in membrane protein genes such as ANK1 and SPTB. The disease exhibits considerable heterogeneity in both clinical manifestations and age of onset, presenting substantial diagnostic challenges for clinicians, particularly in pediatric cases.Case presentationThe patient was a 29-day-old boy who had experienced persistent anemia and a medical history of neonatal hyperbilirubinemia since birth. Upon admission, the infant lacked typical HS manifestations such as splenomegaly, jaundice, and spherocytosis on the peripheral blood smear. Whole-exome sequencing identified a novel frameshift mutation c.3556delG (EX30, NM_000037.4), resulting in an amino acid alteration p.Glu1186Lysfs*3. Subsequent Sanger sequencing-based family segregation analysis confirmed that this mutation originated from the paternal allele. Based on the characteristic clinical manifestations and genetic findings, a definitive diagnosis of HS was established.ConclusionsIn neonates presenting with unexplained recurrent anemia, particularly those with a history of neonatal hyperbilirubinemia, HS should be suspected. Due to the atypical manifestations, genetic analysis serves as a pivotal tool in the early diagnosis of HS, and novel genetic mutations may be identified, which can subsequently be added to the genetic database.